Financing Small and Medium Enterprises through Non-Banking Financial Instruments Perceptions of Libyan Market Authority and the National Program for (SMEs) - مرعي الدرباق, أمين; محمد أبوزقية, عبد الناصر (Dirasat in Economics and Business, 2026)
The study aimed to introduce non-banking financing tools, study the reality of financing small and medium enterprises (SMEs) through non-banking financing tools, and the reasons that prevent the use of these tools in financing small and medium enterprises, and find solutions to guide the use of these tools. A qualitative approach was used in collecting and analyzing data. To collect data, interviews were conducted with senior management employees of the National Program for Small and Medium Enterprises and members of the Management Committee of the Capital Market Authority. The study concluded that non-banking financing tools are not used to finance small and medium enterprises for several reasons, the most important of which is the lack of financial culture such as These tools are weak in infrastructure and legislation, political and security instability, and the lack of ready institutions. The study also found a set of solutions that may contribute to activating the use of non-banking financing tools, the most important of which are spreading culture and awareness of non-banking financing tools, developing legislation and regulations, strengthening investment partnerships, developing Electronic financing tools, attracting foreign investment.